Evolutionary Distance Predicts Recurrence After Liver Transplantation in Multifocal Hepatocellular Carcinoma. Issue 10 (October 2018) - Heits, Nils; Brosch, Mario; Herrmann, Alexander; Behrens, Robin; Röcken, Christoph; Schrem, Harald; Kaltenborn, Alexander; Klempnauer, Jürgen; Kreipe, Hans-Heinrich; Reichert, Benedikt; Lenschow, Christina; Wilms, Christian; et al.
Abstract : Background: Liver transplantation (LTx) is a potentially curative treatment option for hepatocellular carcinoma (HCC) in cirrhosis. However, patients, where HCC is already a systemic disease, LTx may be individually harmful and has a negative impact on donor organ usage. Thus, there is a need for improved selection criteria beyond nodule morphology to select patients with a favorable outcome for LTx in multifocal HCC. Evolutionary distance measured from genome-wide single-nucleotide polymorphism data between tumor nodules and the cirrhotic liver may be a prognostic marker of survival after LTx for multifocal HCC. Methods: In a retrospective multicenter study, clinical data and formalin-fixed paraffin-embedded specimens of the liver and 2 tumor nodules were obtained from explants of 30 patients in the discovery and 180 patients in the replication cohort. DNA was extracted from formalin-fixed paraffin-embedded specimens followed by genome wide single-nucleotide polymorphism genotyping. Results: Genotype quality criteria allowed for analysis of 8 patients in the discovery and 17 patients in the replication set. DNA concentrations of a total of 25 patients fulfilled the quality criteria and were included in the analysis. Both, in the discovery ( P = 0.04) and in the replication data sets ( P = 0.01), evolutionary distance was associated with the risk of recurrence of HCC after transplantation (combined P = 0.0002). In a univariate analysis, evolutionary distance ( P = 7.4 × 10 −6 ) and microvascular invasion ( P = 1.31 × 10 −5 ) were significantly associated with survival in a Cox regression analysis. Conclusions: Evolutionary distance allows for the determination of a high-risk group of recurrence if preoperative liver biopsy is considered. Abstract : The authors of this multicenter retrospective study assess whether the evolutionary distance measured from genome-wide single nucleotide polymorphism (SNP) data between tumor nodules and the cirrhotic liver may be a prognostic marker of survival after liver transplantation for multifocal hepatocellular carcinoma. Supplemental digital content is available in the text.